An Update Review on Autoimmune Disease - Sahu, Debasish; Dr. Arpita Das (International Journal of Psychosocial Rehabilitation, 2019)
Autoimmune diseases are the pathological conditions which are identified by the abnormal autoimmune responses and characterized by the reactivity of the immune system by auto antibodies and T-cell responses to self-molecules. Rheumatoid arthritis, vasculitis and systemic lupus erythematosus (lupus) are some other severe autoimmune disorders. Human autoimmune diseases (AD) frequently occur (in general, affecting higher than 5% of the world’s population) and put a major burden on the human population of morbidity and mortality. AD is characterized as diseases in which the immune response to particular self-antigens leads to the ongoing damage to the tissue that occurs in that state. ADs can either be tissue-specific (e.g., thyroid, pancreatic β-cells), aimed at particular tissue specific antigens, or even more systemic affecting several tissues, and targeting a range of seemingly widely expressed autoantigens. Autoimmune diseases are some of the leading causes of death and injury in females below the age of 65. Autoimmune disease development depends on a combination of the environmental and genetic factors. A more practical distinction distinguishes between disorders in which the proliferation, death or regulation of T or B cells is normally altered and those in that an aberrant reaction to a single antigen, whether self-related or foreign, induces autoimmunity.